Pengaruh Model Pembelajaran Kooperatif Tipe STAD (Student Team Achievement Division) Terhadap Hasil Belajar Matematika Pada Materi Pengolahan Data Peserta Didik Kelas V MI Miftahul Ulum - Masyona Masyona; Yhasinta Agustyarini (MISOOL: Jurnal Pendidikan Dasar, 2023)
Matematics is one of the obligation lesson that must be thaught from the basic class (Elementary School) to the high classes (Junior and Senior High Schools). In fact, matematics is still guessed as the hard lesson, this statement was proved by the result of PISA (Programme International Student Assesment) on the year of 2018, and Indonesia placed on the-72 position of 79 participant countries. Since then, the problem was found that Learning method is still using monotonous learning method. The cooperative learning model, with using STAD (Student Team Achievement Division) type, is a model which students have a good team work and doing actively in learning. The purpose of this research is about knowing the influence of the cooperative learning model, with using STAD (Student Team Achievement Division) type on the results of learning about the data display of matematics lesson, which lesson is learned by the students class V. The kind of this result is kuantitatif with using the model of One Group Pretest Posttest Design research, using the research sample of 12 students who were given any treatments. The result of wilcoxon data analysis which based on the Asymp values. Sig. (2-tailed) and also has a value of 0,003 is on the double choice questions, and the value of essay questions have 0.002 < 0,05, which means that “alternative hyphoteses is accepted”, and the result can be inferred that there is the influence of applying the cooperative which type is STAD (Student Team Achievement Division) model on the results of learning about the data display of matematics lesson, which lesson is learned by the students class V.